Politik Identitas Dan Tantangan Hubungan Antar Agama Di Indonesia - Ruslan, Idrus; Hakiki, Kiki Muhamad (AL-ADYAN, 2022)
The problem of inter-religious relations, especially in Indonesia, is actually always related to human life. This condition demands openness and community readiness to respect each other and accept all forms of interreligious relations. However, the existence of inter-religious relations turns out to make people trapped in group ambitions and deny other groups. In the current context, this phenomenon is categorized as the strengthening of identity politics in society. This study uses a qualitative approach that relies on sources of library data in the form of scientific texts, both printed and online, which are described by analyzing the issue of identity politics and inter-religious relations in Indonesia in depth and objectively. The results of this study reveal; there are still expressions of identity politics in Indonesia that are carried out in an irresponsible and immature manner that can threaten the interreligious relations that have been built. Therefore the expression and articulation of identity politics must be carried out on the basis of universal ideals and common interests.